A Soft Robotic Balloon Endoscope for Airway Procedures - Yingtian Li; Joseph Peine; Margherita Mencattelli; Jiaole Wang; 하준형; Pierre E. Dupont (Mary Ann Liebert, 2022)
Soft robots can provide advantages for medical interventions given their low cost and their ability to change shape and safely apply forces to tissue. This article explores the potential for their use for endoscopically-guided balloon dilation procedures in the airways. A scalable robot design based on balloon catheter technology is proposed, which is composed of five balloons together with a tip-mounted camera and LED. Its design parameters are optimized with respect to the clinical requirements associated with balloon dilation procedures in the trachea and bronchi. Possessing a lumen to allow for respiration and powered by the pressure and vacuum sources found in a clinical procedure room, the robot is teleoperated through the airways using a game controller and real-time video from the tip-mounted camera. The robot design includes proximal and distal bracing balloons that expand radially to produce traction forces. The distal bracing balloon is also used to perform balloon dilation. Three actuation balloons, located between the bracing balloons, produce elongation and bending of the robot body to enable locomotion and turning. An analysis of the actuation balloons, which incorporate helical coils to prevent radial collapse, provides design formulas by relating geometric parameters to such performance criteria as maximum change in actuator length and maximum robot bending angle. Experimental evaluation of a prototype robot inside rigid plastic tubes and ex vivo porcine airways is used to demonstrate the potential of the approach.